Online recognition system for handwritten Arabic chemical symbols - Abuzaraida, Mustafa Ali; Zeki, Akram M.; Zeki, Ahmed M.; Za'bah, Nor Farahidah (2014)
Arabic chemical symbols are remarkably different from Latin chemical symbols which written by Arabic characters. On the other hand, Arabic chemical symbols follow Latin chemical symbols from the structure of writing the symbols. Although, Arabic symbols have special way of the writing like writing direction, cursive style, and written by Arabic characters. In fact, these symbols are being used in schools and high education level around many Arabic countries. In this paper an online system for recognizing handwritten Arabic chemical symbols is presented. The paper illustrates each phase of the system in details. The system is dealing with some Arabic chemical symbols as initial study and to be updated with more symbols later.